Inflation and unemployment - Morley, Samuel A. (Hinsdale, Ill. : Dryden Press, 1979)
One of the principal purposes of this book is to develop a simple economic framework that will generate the two-phase inflationary process. The framework relies heavily on inflation expectations by labour, and has now come to be known as the expectations model of inflation.
First published in 1971 under title: The economics of inflation.
Includes bibliographies.
osc 08/08/2018
Loans
Keywords: Inflation (Finance) and unemployment